Traffic Noise Absorption and Propagation in A Three-Dimensional Spatial Environment - Nevil Vidyamanee Wickramathilaka; Uznir Ujang; Suhaibah Azri; Tan Liat Choon; Attygalage Ranjith Rupasinghe (Geoplanning: Journal of Geomatics and Planning)
The impact of noise barriers on noise propagation is vital for traffic noise calculations and visualizations. Noise barriers create a major noise reduction. Green belts are the most common type of noise barrier to mitigate road traffic noise. The width, height, and surface area of leaves a green belt, as well as the noise absorption coefficient of leaves, are vital for noise absorption. This review aims to compare the characteristics and performance of green belts barriers built for traffic noise reduction. Individual tree canopies play the main role in absorbing noise in green belts. Therefore, identifying the canopy's properties is important. The side scan and nadir scan from the LiDAR survey were used to detect the tree canopy points cloud. The voxel-based, convex hull, and concave hull methods are used to visualize tree canopies in three-dimensional (3D). Concave hull provides an extract fitting surface than convex hull visualization. However, these hull surfaces do not provide accurate estimation of surface area of leaves. Further, voxel-based horizontal layers through the voxel-based profiling describes a significant method to calculate surface area of leaves in tree canopies. Establishing green belts as barriers is more cost-effective, making the former better for developing countries.